Mechanism and Application of Reverse Austenitic Transformation in Medium Mn Steels: A Systematic Review. Issue 10 (22nd June 2022) - Guo, Qinyi; Hu, Bin; Luo, Haiwen
Abstract : In this contribution, the nucleation and growth mechanism of austenite during the intercritical annealing (IA) of medium Mn steels (MMSs) are reviewed. The nucleation of austenite can be enhanced due to the introduction of (sub)grain boundaries, dislocations, and carbides before austenitization. Although martensite may transform to austenite in a displacive way during flash heating, austenitic nuclei usually grow with the diffusion and partitioning of solute C/Mn atoms. The latter, however, is still difficult to be modeled because the combined influence of interface dissipation energy, defects, and carbide particles is not well understood and quantified. Next, four recent emerging processing technologies, including prior deformation for generating dislocations, additional tempering for the precipitation of carbides, additional annealing before IA, and flash heating, are also analyzed according to the above‐stated nucleation and growth mechanism. Finally, it is proposed that the targeted austenite grains for improving the mechanical properties of MMS shall be produced by enhancing both nucleation sites and growth kinetics of austenite via the deliberate design of processing routes. Abstract : The reverse austenitic transformation plays a critical role in both the fraction and the stability of retained austenite and then the resultant mechanical properties of medium Mn steels. This contribution reviews the austenitic nucleation and growth mechanisms during the reverse transformation and several processing strategies that have recently emerged for improving mechanical performance by utilizing these mechanisms.